Principal component and hierarchical cluster analysis to select hurdle technologies for minimal processed radishes - Goyeneche, Rosario (2014)
The application of principal component and hierarchical cluster analysis as a mathematical tool to select hurdle technologies (physical and chemical) to inhibit polyphenol oxidase (PPO) activity and color stability of minimally sliced radishes was presented. Results of PPO activity and color were reported initially (day zero) and after 4 d of refrigerated storage. Based on the mentioned tools and from the thirteen mono-hurdles technologies that were initially selected, eight hurdles were chosen as the best and combined in pairs. From those hurdles, the following double-hurdles were selected as those capable of retaining the product color: Ascorbic Acid (AA) + Acetic Acid (ACA-05), AA + NaCl-1, ACA-05+NaCl-1, AA + Heat Treatment (TT-501), ACA-05 + Ultrasound (US), Citric Acid (CA) + AA, CA + ACA-05, NaCl-1+US. When comparing the best mono-hurdles (AA, TT-501, NaCl-1) to the best double hurdles, the following hurdles: AA, TT-501, CA + ACA-05, NaCl-1+US, CA + AA and NaCl-1 were chosen as those capable of maintaining the typical color of radish slices with acceptable sensory parameters and enzyme inhibition after 4 d of storage.